Photon Statistics of Incoherent Cathodoluminescence with Continuous and Pulsed Electron Beams - Sola-Garcia, Magdalena; Mauser, Kelly W.; Liebtrau, Matthias; Coenen, Toon; Christiansen, Silke; Meuret, Sophie; Polman, Albert (ACS Photonics, 2021)
Photon bunching in incoherent cathodoluminescence (CL) spectroscopy originates from the fact that a single high-energy electron can generate multiple photons when interacting with a material, thus, revealing key properties of electron-matter excitation. Contrary to previous works based on Monte Carlo modeling, here we present a fully analytical model describing the amplitude and shape of the second order autocorrelation function (g(2)(τ)) for continuous and pulsed electron beams. Moreover, we extend the analysis of photon bunching to ultrashort electron pulses, in which up to 500 electrons per pulse excite the sample within a few picoseconds. We obtain a simple equation relating the bunching strength (g(2)(0)) to the electron beam current, emitter decay lifetime, pulse duration, in the case of pulsed electron beams, and electron excitation efficiency (γ), defined as the probability that an electron creates at least one interaction with the emitter. The analytical model shows good agreement with the experimental data obtained on InGaN/GaN quantum wells using continuous, ns-pulsed (using beam blanker) and ultrashort ps-pulsed (using photoemission) electron beams. We extract excitation efficiencies of 0.13 and 0.05 for 10 and 8 keV electron beams, respectively, and we observe that nonlinear effects play no compelling role, even after excitation with ultrashort and dense electron cascades in the quantum wells.
CRIS-Team Scopus Importer:2023-03-07
Keywords: autocorrelation measurements; bunching; cathodoluminescence; photon statistics; quantum wells